CASE REPORT: DESMOID TUMOR OF THE BREAST - Horta, Luciana Carvalho; Silveira, Fabia Beraldo; Alvarenga, Bruno Henrique; Jácome, Anna Carolina Pereira; Lima, Juliana Cristina de Oliveira (Mastology, 2020)
Desmoid tumors are neoplasms that originate from fascial or musculoaponeurotic structures, constituted by fibroblast proliferation. It has no metastatic or differentiation potential, but is locally aggressive and has high rates of recurrence even after complete resection. It represents 0.03% of all neoplasms. This study aimed at reporting a rare clinical case of a young patient diagnosed with a desmoid tumor of the breast after a silicone implant surgery.